Contemporary fiqh framework in the era of digital transformation: New challenges and opportunities - Jundi Soehardin Abdullah; Muhammad Jailani; Husna Nashihin (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
This study examines the framework of contemporary fiqh in the era of digital transformation, focusing on how Islamic law adapts to social, technological, and communicative changes within the Muslim community. Digitalization has reshaped religious authority, fatwa-issuing methods, and the dynamics of legal understanding in public spaces. Phenomena such as online fatwas, AI muftis, and digital religious content demand methodological reconstruction so that fiqh remains relevant to the context of the time without compromising its foundational principles of the Sharia. This study employs a qualitative descriptive-analytical approach through a literature review of journals and academic publications from the past five years that discuss the intersection between fiqh, technology, and maqāṣid al-sharī‘ah. Through content and thematic analysis, findings indicate that technological development has given rise to digital-maqāṣidī fiqh, a model of Islamic law that emphasizes public benefit (maṣlaḥah), digital ethics, and adaptability to technological innovation. Digital transformation offers broad opportunities for the dissemination of Islamic law but also raises challenges regarding religious authority and the validity of legal sources. Therefore, synergy between scholars, academics, and policymakers is required to build an ethical, collaborative, and maqāṣid-oriented digital fiqh ecosystem as the foundation for the future of Islamic law.